Konsep kesediaan keusahawanan berdasarkan kajian kes usahawan industri kecil dan sederhana (IKS) di Malaysia - Norashidah Hashim,; Norasmah Othman,; Noraishah Buang, (penerbit ukm, 2009)
This research explored the conceptual definition of entrepreneurial readiness based on case study of six Small Medium Industri (SMI) entrepreneurs in various industries career path experience in Malaysian context. The result of data collected from interviews showed that the conceptual definition of entrepreneurial readiness consists of two major categories: willingness and ability. The elements of entrepreneurial willingness are attitude, spiritual strength and willingness to learn. The elements of entrepreneurial readiness are entrepreneurial thinking, entrepreneur vocational skill and entrepreneurial knowledge. This multi dimension entrepreneurial readiness taxanomy can be used to assist to identify the readiness elements of an individual in order to prepare them for career as entrepreneurs.